2015
DOI: 10.7567/jjap.54.076501
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ni mold for nanoimprint lithography by combining two supercritical fluid-based deposition technologies

Abstract: Hollow-core toroidal micro-cavities are obtained by self-rolling of double-layer (polyvinyl pyridine/polystyrole) polymer films. Rolling of the bilayer is due to preferential swelling of polyvinyl pyridine in water solution of dodecyl benzene sulfonic acid. The tube formation proceeds from a circular opening in the film made by photolithography or by mechanical scratching. Toroid equilibrium dimensions are determined by the balance of the elastic energy relaxation via the film scrolling and the work of the in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…[189] Very recently, it has been shown that SCFD of Ni on polymer resists can be achieved by depositing a thin layer of Pd first as shown in Figure 12. [190] Deposition of the Pd film was achieved by supercritical fluid impregnation (SCFI) at 150 °C. The advantage of this method is the low process temperature (>200 °C) which is essential as the photoresist is sensitive to temperature.…”
Section: Preparation Of Metallic Thin Films Using Sccomentioning
confidence: 99%
“…[189] Very recently, it has been shown that SCFD of Ni on polymer resists can be achieved by depositing a thin layer of Pd first as shown in Figure 12. [190] Deposition of the Pd film was achieved by supercritical fluid impregnation (SCFI) at 150 °C. The advantage of this method is the low process temperature (>200 °C) which is essential as the photoresist is sensitive to temperature.…”
Section: Preparation Of Metallic Thin Films Using Sccomentioning
confidence: 99%